The BUDGET RATCHETING, ORIGINAL LOCAL GOVERNMENT REVENUE ORIGINAL LOCAL GOVERNMENT REVENUE, FISCAL BALANCE FUND ON CAPITAL EXPENDITURE ALLOCATIONS IN INDONESIA - Gede Teguh Prasetya Muttiwijaya; I Dewa Gede Anom Jambe Adnyana; Komang Tri Yasrawan; I Made Pradana Adiputra (KRISNA: Kumpulan Riset Akuntansi, 2026)
The implementation of regional autonomy enables local governments to independently manage various activities aimed at enhancing regional welfare, including financial management that is more community-oriented. In Indonesia, nearly all regional governments revise their budgets annually, making the examination of changes in capital expenditure budgets a compelling area of study. This research seeks to investigate the role of budget ratcheting in moderating the relationship between local revenue and balancing funds with capital expenditure allocation in Indonesia. The study utilizes secondary data comprising financial statements, specifically the regional revenue and expenditure budgets and budget realization reports published by respective local governments over a five-year period (2019–2023). Data analysis is conducted using hierarchical linear regression techniques. This research adopts a causative design and a quantitative methodological approach. Partially, Local Own-Source Revenue and Balance Funds have a positive and significant effect on capital expenditure allocation, while Budget Ratcheting does not moderate this relationship. This implies local governments must consider both external and internal conditions (uncertainty) when formulating budgets. Therefore, the budget should not always be based solely on past achievements, particularly for PAD, balance funds, and capital expenditure, which cannot be planned only based on previous performance.